A new method to measure electroretinograms (ERGs) elicited by temporal white noise - Kremers, Jan; Feigl, Beatrix K.; Aher, Avinash; Mckeefry, Declan J.; Parry, Neil Robert Alan; Maguire, John; Murray, Ian J.; Zele, Andrew J. (Investigative Ophthalmology & Visual Science, 2017)

A Temporal White Noise Analysis for Extracting the Impulse Response Function of the Human Electroretinogram - Zele, Andrew J.; Feigl, Beatrix; Kambhampati, Pradeep K.; Aher, Avinash; Mckeefry, Declan; Parry, Neil; Maguire, John; Murray, Ian; Kremers, Jan (Translational Vision Science & Technology, 2017)
Purpose: We introduce a method for determining the impulse response function (IRF) of the ERG derived from responses to temporal white noise (TWN) stimuli.Methods: This white noise ERG (wnERG) was recorded in participants with normal trichromatic vision to full-field (Ganzfeld) and 39.3 degrees diameter focal stimuli at mesopic and photopic mean luminances and at different TWN contrasts. The IRF was obtained by cross-correlating the TWN stimulus with the wnERG.Results: We show that wnERG recordings are highly repeatable, with good signal-tonoise ratio, and do not lead to blink artifacts. The wnERG resembles a flash ERG waveform with an initial negativity (N1) followed by a positivity (P1), with amplitudes that are linearly related to stimulus contrast. These N1 and N1-P1 components showed commonalties in implicit times with the a-and b-waves of flash ERGs. There was a clear transition from rod-to cone-driven wnERGs at similar to 1 photopic cd.m(-2). We infer that oscillatory potentials found with the flash ERG, but not the wnERG, may reflect retinal nonlinearities due to the compression of energy into a short time period during a stimulus flash.Conclusion: The wnERG provides a new approach to study the physiology of the retina using a stimulation method with adaptation and contrast conditions similar to natural scenes to allow for independent variation of stimulus strength and mean luminance, which is not possible with the conventional flash ERG.
Keywords: electroretinogram (ERG); temporal white noise; impulse response function

Comparison of macaque and human L- and M-cone driven electroretinograms - Kremers, Jan; Aher, Avinash; Parry, Neil R.A.; Patel, Nimesh B.; Frishman, Laura J. (Experimental Eye Research, 2021)
Purpose: The macaque retina is often used as a model for the human retina. However, there are only a handful of direct in vivo comparisons of the retinal physiology in humans and macaques. In the current study, ERG responses to luminance, L-cone isolating and M-cone isolating stimuli with sinusoidal, sawtooth and square wave temporal profiles were measured. The results were compared with those obtained from human observers. Methods: The responses from five anesthetized adult macaques were measured. Full field stimuli were created. L- and M-cone isolating stimuli were based on the triple silent substitution technique. Sinusoidal stimuli had temporal frequencies between 4 and 56 Hz in 4 Hz steps. Sawtooth stimuli with rapid-on ramp-off and with rapid-off ramp-on excitation profiles had a frequency of 4 Hz. Square stimuli were presented at 2 Hz. Results: Macaque and human ERGs in response to L- and M-cone isolating stimuli reflect L/M opponency and luminance activity. In responses to sine waves, cone opponency dominates at low temporal frequencies (4–12 Hz); luminance dominates at high temporal frequencies. The responses to sawtooth and square wave stimuli reflect a mixture of chromatic and luminance activity. L:M response ratios vary between individuals both in macaques and humans. Macaques show more complex responses, including greater second harmonic contributions than those in humans. Conclusions: Macaque and human ERGs share basic underlying mechanisms reflecting L/M opponency and luminance activity. There may be quantitative differences possibly reflecting differences in contributions of inner retinal mechanisms to the ERGs.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Cone opponency; Electroretinogram; Human; L-cones; Luminance; M-cones; Macaque

Electrodiagnosis of dichromacy - Barboni, Mirella Telles Salgueiro; Hauzman, Einat; Nagy, Balázs Vince; Martins, Cristiane Maria Gomes; Aher, Avinash; Tsai, Tina I.; Bonci, Daniela Maria Oliveria; Ventura, Dora Fix; Kremers, Jan (Vision research, 2019)
Retinal and cortical signals initiated by a single cone type can be recorded using the spectral compensation (or silent substitution) paradigm. Moreover, responses to instantaneous excitation increments combined with gradual excitation decreases are dominated by the response to the excitation increment. Similarly, the response to a sudden excitation decrement dominates the overall response when combined with a gradual excitation increase. Here ERGs and VEPs were recorded from 34 volunteers [25.9 ± 10.4 years old (mean ± 1 SD); 25 males, 9 females] to sawtooth flicker (4 Hz) stimuli that elicited L- or M-cone responses using triple silent substitution. The mean luminance (284 cd/m 2 ) and the mean chromaticity (x = 0.5686, y = 0.3716; CIE 1931 color space) remained constant and thus the state of adaptation was the same in all conditions. Color discrimination thresholds along protan, deutan, and tritan axes were obtained from all participants. Dichromatic subjects were genetically characterized by molecular analysis of their opsin genes. ERG responses to L-cone stimuli were absent in protanopes whereas ERG responses to M-cone stimuli were strongly reduced in deuteranopes. Dichromats showed generally reduced VEP amplitudes. Responses to cone-specific stimuli obtained with standard electrophysiological methods may give the same classification as that obtained with the Cambridge Colour Test and in some cases with the genetic analysis of the L- and M-opsin genes. Therefore, cone-specific ERGs and VEPs may be reliable methods to detect cone dysfunction. The present data confirm and emphasize the potential use of cone-specific stimulation, combined with standard visual electrodiagnostic protocols.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Color vision; Cone-isolating stimulus; Electroretinogram; Opsin gene; Silent substitution; Spectral compensation; Visual evoked potential

Electroretinographical determination of human color vision type - Aher, Avinash; Martins, Cristiane M. G.; Barboni, Mirella T. S.; Nagy, Balazs V.; Hauzman, Einat; Bonci, Daniela M. O.; Ventura, Dora F.; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
It has been previously demonstrated that electroretinography (ERG) elicited by heterochromatically modulated stimuli can be used for objective determination of color vision type. Color vision of trichromatic, deuteranopic, and protanopic participants was psychophysically assessed by the Cambridge Color Test and confirmed genetically. ERG responses to red and green lights modulating in counterphase at 12 and 36 Hz were recorded, while the fraction of red modulation was varied. At 36 Hz (and second harmonics at 12 Hz), the responses were minimal at red fractions that differed significantly in protanopes. At 12 Hz (fundamental component), the responses of the trichromats differed significantly compared to those of the dichromats. An improved protocol shows that the three subject groups can be separated with no overlap. (C) 2018 Optical Society of America

Electroretinographic responses to luminance and cone-isolating white noise stimuli in macaques - Kremers, Jan; Aher, Avinash; Parry, Neil R. A.; Patel, Nimesh B.; Frishman, Laura J. (Frontiers in Neuroscience, 2022)
Electroretinograms (ERGs) are mass potentials with a retinal origin that can be measured non-invasively. They can provide information about the physiology of the retina. Often, ERGs are measured to flashes that are highly unnatural stimuli. To obtain more information about the physiology of the retina, we measured ERGs with temporal white noise (TWN) stimuli that are more natural and keep the retina in a normal range of operation. The stimuli can be combined with the silent substitution stimulation technique with which the responses of single photoreceptor types can be isolated. We characterized electroretinogram (ERG) responses driven by luminance activity or by the L- or the M-cones. The ERGs were measured from five anesthetized macaques (two females) to luminance, to L-cone isolating and to M-cone isolating stimuli in which luminance or cone excitation were modulated with a TWN profile. The responses from different recordings were correlated with each other to study reproducibility and inter-individual variability. Impulse response functions (IRFs) were derived by cross-correlating the response with the stimulus. Modulation transfer functions (MTFs) were the IRFs in the frequency domain. The responses to luminance and L-cone isolating stimuli showed the largest reproducibility. The M-cone driven responses showed the smallest inter-individual variability. The IRFs and MTFs showed early (high frequency) components that were dominated by L-cone driven signals. A late component was equally driven by L- and M-cone activity. The IRFs showed characteristic similarities and differences relative to flash ERGs. The responses to TWN stimuli can be used to characterize the involvement of retinal cells and pathways to the ERG response. It can also be used to identify linear and non-linear processes.
CRIS-Team WoS Importer:2022-09-02

ERG responses and the Ferry-Porter law - Kremers, Jan; Aher, Avinash; Huchzermeyer, Cord (Journal of the Optical Society of America A: Optics and Image Science, and Vision, 2025)
The Ferry-Porter law states that the psychophysically measured critical flicker fusion frequency (CFF) is linearly correlated with the logarithm of the mean luminance. We studied the relationship between the CFFs of L- and M-cone driven ERGs (five normal trichromats; sinusoidal modulation; 18% cone contrast) and mean luminance. The measurements were performed at seven mean luminances between 2.84 and 284 cd/m2. Close to the CFF, the ERG amplitudes versus temporal frequency could be described by a simple exponential function. The CFFs were higher for L- than for M-cone driven ERGs and depended linearly on the logarithm of the mean luminance (i.e., adhered to the Ferry-Porter law) with steeper slopes compared to psychophysical measurements.
CRIS-Team Scopus Importer:2025-05-02

ERG signals elicited by temporal white noise in macaques - Kremers, Jan; Aher, Avinash; Parry, Neil; Patel, Nimesh Bhikhu; Frishman, Laura J. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

High-frequency characteristics of L- and M-cone driven electroretinograms - Aher, Avinash; Jacob, Mellina M.; Kremers, Jan (Vision research, 2019)
Electroretinograms (ERGs) elicited by high temporal frequency (26–95 Hz) L- and M-cone isolating sine-wave stimuli were investigated in human observers for full-field (FF) and different spatially restricted stimulus sizes (70°, 50°, 30°, and 10° diameter). Responses to L- and M-cone isolating FF stimuli were maximal around 48 Hz and decreased gradually with increasing temporal frequency up to 95 Hz. The response maximum was shifted to about 30–32 Hz for both L- and M-cone driven responses obtained with spatially restricted stimuli. The M-cone driven responses could only be measured up to 54 Hz with 70° stimuli. The response amplitudes for L- and M-cones and L-/M-cone amplitude ratios decreased with decreasing stimulus size. The ERG response phases to L- and M-cone isolating stimuli decreased with increasing temporal frequency and were about −160° apart for all stimulus sizes up to 34 Hz. Further increase in the temporal frequency displayed a positive correlation between stimulus size and L-M phase difference. The ERG data indicate that the responses evoked by high temporal frequency cone isolating stimuli reflect two mechanisms, one that is more centrally located and displays a maximum at about 30–32 Hz and a peripheral mechanism that is sensitive to higher temporal modulations. We propose that the peripheral mechanism (FF ERGs) reflects magnocellular activity, whereas the central mechanism (ERGs with spatially restricted stimuli) is based on a parvocellular activity up to about 30 Hz.
CRIS-Team Scopus Importer:2019-05-16
Keywords: Electroretinograms; Magnocellular; Parvocellular; Stimulus size; Temporal frequency

Linking ERG recordings to psychophysical data in human subjects - Kremers, Jan; Aher, Avinash; Stuewe, Karin (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-24

L-/M-cone opponency in visual evoked potentials of human cortex - Salgueiro Barboni, Mirella Telles; Nagy, Balazs Vince; Gomes Martins, Cristiane Maria; Oliveria Bonci, Daniela Maria; Hauzman, Einat; Aher, Avinash; Tsai, Tina I.; Kremers, Jan; Ventura, Dora Fix (Journal of Vision, 2017)
L and M cones send their signals to the cortex using two chromatic (parvocellular and blue-yellow koniocellular) and one luminance (magnocellular) pathways. These pathways contain ON and OFF subpathways that respond to excitation increments and decrements respectively. Here, we report on visually evoked potentials (VEP) recordings that reflect L- and M-cone driven increment (LI and MI) and decrement (LD and MD) activity. VEP recordings were performed on 12 trichromats and four dichromats (two protanopes and two deuteranopes). We found that the responses to LI strongly resembled those to MD, and that LD and MI responses were very similar. Moreover, the lack of a photoreceptor type (L or M) in the dichromats led to a dominance of the ON pathway of the remaining photoreceptor type. These results provide electrophysiological evidence that antagonistic L/M signal processing, already present in the retina and the lateral geniculate nucleus (LGN), is also observed at the visual cortex. These data are in agreement with results from human psychophysics where MI stimuli lead to a perceived brightness decrease whereas LI stimuli resulted in perceived brightness increases. VEP recording is a noninvasive tool that can be easily and painlessly applied. We propose that the technique may provide information in the diagnosis of color vision deficiencies.
EVALuna2:21340

Modulation of flash ERGs by dynamic backgrounds - Kremers, Jan; Aher, Avinash; Huchzermeyer, Cord (Documenta Ophthalmologica, 2022)
Purpose The aim of this study was to characterize the signal processing mechanisms that lead to an ERG response and to use this characterization for obtaining more robust responses in patients who display feeble responses with standard recordings. We studied the influence of sinusoidally modulating backgrounds on flash ERGs and the relationship between the ERG components' amplitudes and the momentary Weber fraction of the flash stimulus. Methods ERG recordings were performed in nine healthy subjects and three RP patients. In four normal subjects, we measured the response to flashes (500 cd/m(2), 1 ms duration) on a steady background (50 cd/m(2)) and on a sine wave (50 cd/m(2) mean luminance) modulating background at 1, 5, 10, and 25 Hz temporal frequencies. The flashes were delivered at eight different phases (0-315 degrees in a step of 45 degrees) during the modulating background sine wave. The responses to the backgrounds were also recorded and subtracted from the responses to flash plus modulating backgrounds to obtain the flash ERGs at the different phases. The recordings in the remaining five normal subjects and the RP patients were performed with a subset of these stimuli. Results The flash ERGs were strongly modulated by the backgrounds particularly at low frequencies and were enhanced when the momentary Weber fraction was large. The amplitudes of the components could be described by the Weber fraction plus a saturating nonlinearity and a delay in the processing of background luminance. The strength of the modulation decreased with increasing peak time of the component. Furthermore the background luminance delay was positively correlated with the peak time. The effect was also present in RP patients. Conclusions A sine wave background of about 1 Hz can be used to enhance ERG responses. Weber fraction of the flashes is an adequate quantification of stimulus for describing the amplitudes of the ERGs. The data provide basic information on how background luminance is processed in ERG generating mechanisms. The response enhancement can be used in clinical applications to obtain a more robust comparison between normal and patient data.
CRIS-Team WoS Importer:2022-11-04

Relationship between stimulus size and different components of the electroretinogram (ERG) elicited by flashed stimuli - Nittmann, Mathias; Aher, Avinash; Kremers, Jan; Tzekov, Radouil T. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Relationship between stimulus size and different components of the electroretinogram (ERG) elicited by flashed stimuli - Nittmann, Mathias G.; Aher, Avinash; Kremers, Jan; Tzekov, Radouil (Documenta Ophthalmologica, 2020)
Purpose: To investigate how light stimulus conditions of varying spatial sizes affect components of the flash and long-flash electroretinogram (ERG) in normal subjects. Method: Three stimulus conditions were generated by a Ganzfeld stimulator: a white flash on white background (WoW), a red flash on a blue background (RoB) and an L+M-cone isolating on–off (long flash) stimulus (Cone Iso). ERGs were recorded from six subjects (5 M, 1 F) with DTL electrodes to full-field (FF), 70°, 60°, 50°, 40°, 30° and 20° diameter circular stimuli. Amplitudes and peak times for a-, b-, d- and i-wave, and PhNR were examined. PhNR amplitudes were estimated in two different ways: from baseline (fB) and from preceding b-wave peak (fP). Results: With decreasing stimulus size, amplitudes for all ERG waveform components attenuated and peak times increased, although the effect varied across different components. An exponential fit described the relationship between amplitudes and size of stimulated retinal area well for most components and conditions (R2= 0.75-0.99), except for PhNR(fB) (R2= − 0.16–0.88). For peak times, an exponential decay function also fitted the data well (R2= 0.81–0.97), except in a few cases where the exponential constant was too small and a linear regression function was applied instead (a-wave Cone Iso, b- and i-wave WoW). The exponential constants for RoB amplitudes (b-wave, PhNR(fB), PhNR(fP)) were larger compared to their counterparts under WoW (p < 0.05), while there was no difference between the constants for a-wave amplitudes and peak times and for PhNR peak times. The exponential constants of amplitudes vs. area under WoW and Cone Iso were remarkably similar, while under RoB PhNR(fB) showed larger constants compared to either a- or b-wave (p < 0.05). Conclusion: ERG components change in a predictable way with stimulus size and spectral characteristics of the stimulus under these conditions. This predictability could allow a modified version of these sets of stimuli to be tested for clinical applicability.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Electroretinogram; Flash stimuli; Photopic negative response; Square wave stimuli; Stimulus size

Responses of postreceptoral pathways elicited by L- And M-cone isolating ON- And OFF-electroretinograms in glaucoma patients - Aher, Avinash; Horn, Folkert; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2021)
PURPOSE. To compare the electroretinographical (ERG) responses elicited by L- and M-cone isolating ON- and OFF-sawtooth stimuli in normal subjects and glaucoma patients. METHODS. Twenty-one normal subjects and 44 primary open-angle glaucoma patients participated in the study. L- and M-cone isolating (18% cone contrast; 284 cd/m2) rapid ON- and rapid OFF-sawtooth (4 Hz) stimuli with two stimulus sizes (full-field (FF) and central 70° diameter) were generated using the triple silent substitution technique. ON- and OFF-response asymmetries were studied by adding the two (to obtain L-add and M-add responses). The initial positive (P) and subsequent late negative (LN) components of the L-add and M-add ERGs were compared between the subject groups and correlated with retinal nerve fiber layer thickness (RNFLT) and pattern ERG responses. RESULTS. The responses to L-ON and to M-OFF stimuli and vice versa resembled each other particularly with 70° stimuli. The PL-add amplitudes were not significantly different between the normal subjects and glaucoma patients, whereas the LNL-add amplitude was significantly (P < 0.01) smaller in the glaucoma patients. Both PM-add and LNM-add were not significantly different between the subject groups. The PERG amplitude with 0.8° check sizes and the 0.8°/16° amplitude ratio (PERG ratio) were significantly (P < 0.05) different between the subject groups. The 70° LNL-add amplitude and the 0.8° PERG amplitude were significantly correlated with RNFLT. CONCLUSIONS. The ERGs to 70° cone isolating sawtooth stimuli reflect cone opponency. The cone opponent ERG responses were not significantly different between glaucoma patients and normal subjects. Luminance driven L-add responses were significantly different, indicating that central luminance signals are mainly affected in glaucoma.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Glaucoma; Magnocellular; ON- and OFF electroretinogram; Parvocellular; Sawtooth stimuli; Silent substitution; Stimulus size

Rod- versus cone-driven ERGs at different stimulus sizes in normal subjects and retinitis pigmentosa patients - Aher, Avinash; Mckeefry, Declan J.; Parry, Neil R. A.; Maguire, John; Murray, I. J.; Tsai, Tina I.; Huchzermeyer, Cord; Kremers, Jan (Documenta Ophthalmologica, 2018)
Purpose To study how rod- and cone-driven responses depend on stimulus size in normal subjects and patients with retinitis pigmentosa (RP), and to show that comparisons between responses to full-field (FF) and smaller stimuli can be useful in diagnosing and monitoring disorders of the peripheral retina without the need for lengthy dark adaptation periods.Method The triple silent substitution technique was used to isolate L-cone-, M-cone- and rod-driven ERGs with 19, 18 and 33% photoreceptor contrasts, respectively, under identical mean luminance conditions. Experiments were conducted on five normal subjects and three RP patients. ERGs on control subjects were recorded at nine different temporal frequencies (between 2 and 60 Hz) for five different stimulus sizes: FF, 70A degrees, 60A degrees, 50A degrees and 40A degrees diameter circular stimuli. Experiments on RP patients involved rod- and L-cone-driven ERG measurements with FF and 40A degrees stimuli at 8 and 48 Hz. Response amplitudes were defined as those of the first harmonic component after Fourier analysis.Results In normal subjects, rod-driven responses displayed a fundamentally different behavior than cone-driven responses, particularly at low temporal frequencies. At low and intermediate temporal frequencies (<= 12 Hz), rod-driven signals increased by a factor of about four when measured with smaller stimuli. In contrast, L- and M-cone-driven responses in this frequency region did not change substantially with stimulus size. At high temporal frequencies (>= 24 Hz), both rod- and cone-driven response amplitudes decreased with decreasing stimulus size. Signals obtained from rod-isolating stimuli under these conditions are likely artefactual. Interestingly, in RP patients, both rod-driven and L-cone-driven ERGs were similar using 40A degrees and FF stimuli.Conclusion The increased responses with smaller stimuli in normal subjects to rod-isolating stimuli indicate that a fundamentally different mechanism drives the ERGs in comparison with the cone-driven responses. We propose that the increased responses are caused by stray light stimulating the peripheral retina, thereby allowing peripheral rod-driven function to be studied using the triple silent substitution technique at photopic luminances. The method is effective in studying impaired peripheral rod- and cone- function in RP patients.
Keywords: Rods; Cones; Stimulus size; Electroretinogram; Retinitis pigmentosa

Spatial Properties of Electroretinograms Elicited by High Temporal Frequency L- and M-cone Isolating Stimuli - Aher, Avinash; Jacob, Mellina M.; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2019)
CRIS-Team WoS Importer:2019-11-01

Spatial properties of L- and M-cone driven incremental (on-) and decremental (off-) electroretinograms: normal subjects Vs. glaucoma patients - Aher, Avinash; Horn, Folkert; Huchzermeyer, Cord; Lämmer, Robert; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-24

The Association Between Acquired Color Deficiency and PET Imaging of Neurodegeneration in Mild Cognitive Impairment and Alzheimer Disease - Vidal, Kallene Summer Moreira; Decleva, Diego; Barboni, Mirella Telles Salgueiro; Nagy, Balazs Vince; De Menezes, Paulo Augusto Hidalgo; Aher, Avinash; Coutinho, Artur Martins; Squarzoni, Paula; Faria, Daniele De Paula; Duran, Fabio Luis De Souza; Buchpiguel, Carlos Alberto; Kremers, Jan; et al. (Investigative Ophthalmology & Visual Science, 2022)
PURPOSE. To evaluate color vision changes and retinal processing of chromatic and lumi-nance pathways in subjects with Alzheimer disease (AD) and mild cognitive impairment (MCI) compared with a matched control group and whether such changes are associated with impaired brain glucose metabolism and beta-amyloid deposition in the brain.METHODS. We evaluated 13 patients with AD (72.4 +/- 7.7 years), 23 patients with MCI (72.5 +/- 5.5 years), and 18 controls of comparable age (P = 0.44) using Cambridge color test and the heterochromatic flicker ERG (HF-ERG). The Cambridge color test was performed using the trivector protocol to estimate the protan, deutan and tritan color confusion axes. HF-ERG responses were measured at a frequency of 12 Hz, which ERGs reflect chromatic activity, and at 36 Hz, reflecting luminance pathway. A study subsample was performed using neuropsychological assessments and positron emission tomography.RESULTS. Patients with AD presented higher mean values indicating poorer color discrim-ination for protan (P = 0.04) and deutan (P = 0.001) axes compared with the controls. Along the tritan axis, both patients with AD and patients with MCI showed decreased color vision (P = 0.001 and P = 0.001) compared with controls. The analyses from the HF-ERG protocol revealed no differences between the groups (P = 0.31 and P = 0.41). Diffuse color vision loss was found in individuals with signs of neurodegeneration (protan P = 0.002, deutan P = 0.003 and tritan P = 0.01), but not in individuals with signs of beta-amyloid deposition only (protan P = 0.39, deutan P = 0.48, tritan P = 0.63), regardless of their clinical classification.CONCLUSIONS. Here, patients with AD and patients with MCI present acquired color vision deficiency that may be linked with impaired brain metabolism.
CRIS-Team WoS Importer:2023-04-28

The consequence of modulating background on the luminance-response function of the human photopic electroretinogram - Kremers, Jan; Huchzermeyer, Cord; Aher, Avinash (Documenta Ophthalmologica, 2025)
Purpose: To study the consequences of a modulating background on the luminance-response function of the human photopic flash electroretinogram for different relative timings of the flash relative to the background luminance. Methods: Seven healthy subjects (age: 29–63 years; four females) participated in the study. We measured the response to flashes (9 flash strengths in total between 0.12 and 29.76 cd.s/m2 while doubling the strength at each step; 5 ms flash duration) on a steady background (24 cd/m2) and on a 1 Hz modulating background (24 cd/m2 mean luminance; 100% contrast). The flashes were presented at 6 different phases during the sine wave (0°, 90°, 180°, 225°, 270°, and 315°). Responses to a 1 Hz sinusoidally modulating stimulus were subtracted from the responses to the combined flash plus sine-wave stimuli to obtain the flash ERGs at different phases. Results: The a-wave and PhNR amplitudes monotonically increased with increasing flash strength. The b- and i-wave amplitudes displayed a maximum at 1.9 cd.s/m2, above which they decreased again (the so-called “Photopic hill effect”). The responses could be described by an addition of a logistic growth and a Gaussian. The parameters of these functions depended on the time of flash presentation relative to the background. The dependency of the a-, b- and i-wave on flash presentation time with constant flash strength could be described by a model that assumes that the amplitude depends on the Weber fraction of the flash including a delay and a saturation. Conclusions: The use of modulating backgrounds may increase the signal-to-noise ratio of flash ERGs and thus its diagnostic value. The dynamics of the response as a function of flash presentation time gives additional information about the retinal processing of flash and background. The photopic hill model allows the separation of processing in retinal On- and Off-pathways.
CRIS-Team Scopus Importer:2025-06-06
Keywords: ERG; Modulating background; Photopic flash electroretinogram; Photopic hill

The effect of sinusoidally modulating backgrounds on flash electroretinograms - Aher, Avinash; Huchzermeyer, Cord; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

The spatial distribution of ERGs reflecting luminance and L-/M-cone-opponent signals - Vidal, Kallene Summer; Aher, Avinash; Ventura, Dora Fix; Kremers, Jan (Documenta Ophthalmologica, 2021)
Purpose: To study the spatial retinal distribution of electroretinographic (ERG) responses that reflect signals in the L-/M-cone-opponent and luminance post-receptoral pathways. Methods: ERG recordings to heterochromatic stimuli (sinusoidal counter-phase modulation of red and green LED light sources) were performed, while varying fractions of red and green modulation. Two temporal frequencies of the stimuli were employed: 12 Hz to record ERGs that reflect L-/M-cone-opponent signal and 36 Hz for recording ERG signals sensitive to stimulus luminance. Stimuli were about 20° in diameter and projected on various retinal locations: the fovea and four eccentricities (10°, 19°, 28° and 35°), each presented nasally, temporally, inferiorly and superiorly from the fovea. Results: The 36 Hz stimuli elicited responses that strongly varied with red fraction and were minimal at iso-luminance. Moreover, response phases changed abruptly at the minimum by 180°. In contrast, the responses to the 12 Hz stimuli had amplitudes and phases that changed more gradually with red fraction. The 36 Hz response amplitudes were maximal close to the fovea and sharply decreased with increasing distance from the fovea. The responses to 12 Hz stimuli were more broadly distributed across the retina. Conclusions: In the present study, it was found that retinal eccentricity and direction from the fovea have distinct effects on ERGs reflecting different post-receptoral mechanisms. The results are in accord with previous findings that ERGs to 12 Hz stimuli are predominantly determined by the red–green chromatic content of the stimuli, thus reflecting activation in the L-/M-cone-opponent pathway, while responses to 36 Hz stimuli manifest post-receptoral luminance-dependent activation. We found that the response in the cone-opponent pathway is broadly comparable across the retina; in comparison, response amplitude of the luminance pathway strongly depends on retinal stimulus position.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cone opponency; Electroretinography; Luminance; Post-receptoral pathways; Spatial distribution